EVALUATION OF COVID-19 TAX INCENTIVE POLICIES: INCOME TAX ARTICLE 25 AND INCOME TAX ARTICLE 22 IMPORT - Chairunnisa, Nadillah; Nuryanah, Siti (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2023)
The Covid-19 pandemic in 2020 caused the state tax revenue target to not be achieved. Covid-19 Tax Incentives PPh Article 25 and PPh Article 22 Import in 2022 are still being provided by the government because the Covid-19 pandemic has not ended and has had an impact on the economy. The purpose of this research is to evaluate the covid-19 tax incentive policy PPh Article 25 and PPh Article 22 Import from the perception of taxpayers based on The Four Maxims and evaluate the application of the two tax incentive policies at the ABC Tax Office. This research method is mixed, combining quantitative and qualitative approaches. The data in this study were obtained from questionnaires to taxpayers and interviews with tax authorities and taxpayers. The results of the study show that taxpayers' perceptions of tax incentive policies have fulfilled The Four Maxims, but there are still constraints from the web system. The implementation of the Covid-19 tax incentive policy at KPP ABC has been effective, but monitoring, evaluation, and assessment of taxpayer satisfaction have not been carried out as a whole regarding the tax incentive policy.